R-mode constraints from neutron star equation of state - Moustakidis, Ch. C.; Papazoglou, M. C. (HNPS Advances in Nuclear Physics, 2019)
The gravitational radiation has been proposed a long time before, as an explana- tion for the observed relatively low spin frequencies of young neutron stars and of accreting neutron stars in low-mass X-ray binaries as well. In the present work we studied the effects of the neutron star equation of state on the r-mode instability window of rotating neutron stars.